Data for: Thermo-economic Analysis, Optimisation and Systematic Integration of Supercritical Carbon Dioxide Cycle with Sensible Heat Thermal Energy Storage for CSP Application - Thanganadar, Dhinesh; Fornarelli, Francesco; Camporeale, Sergio; Asfand, Faisal; Gillard, Jonathon; Patchigolla, Kumar (Cranfield University, 2021)
Underlying data for the paper "Thermo-economic Analysis, Optimisation and Systematic Integration of Supercritical Carbon Dioxide Cycle with Sensible Heat Thermal Energy Storage for CSP Application"
Keywords: 'Supercritical CO2 cycle'; 'CSP'; 'Overnight Capital Cost'; 'Thermal Energy Storage'; 'Multi-objective optimisation'; 'Central Power Tower'; 'Systematic integration'; 'Power and Energy Systems Engineering (excl. Renewable Power)'; 'Energy Generation; Conversion and Storage Engineering'; 'Renewable Power and Energy Systems Engineering (excl. Solar Cells)'